2016
DOI: 10.1038/srep29675
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation mechanism of 1H-1,2,4-triazole by a newly isolated strain Shinella sp. NJUST26

Abstract: The highly recalcitrant 1H-1,2,4-triazole (TZ) is widely used in the synthesis of agricultural pesticide and considered to be an environmental pollutant. In this study, a novel strain NJUST26 capable of utilizing TZ as the sole carbon and nitrogen source, was isolated from TZ-contaminated soil, and identified as Shinella sp. The biodegradation assays suggested that optimal temperature and pH for TZ degradation by NJUST26 were 30 °C and 6–7, respectively. With the increase of initial TZ concentration from 100 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…This system is also applicable for nitrogen removal in aquaculture, where increased nitrate concentration poses negative effects on fish (51). Indeed, the unclassified Comamonadaceae [AB076847, (42)] and Shinella spp., the intestinal abundance of which increased in response to the fucoidan feeding of adult zebrafish in our current study, have been reported to belong to denitrifying bacteria possessing biodegrading abilities of diverse compounds including biopolymers and xenobiotics (42,52,53). Therefore, it seems plausible that OM fucoidan may serve as a carbon source for intestinal bacteria of adult zebrafish, and identification of the degradation pathways involved awaits further investigation Although a large body of studies has documented that the host innate immunity plays significant roles for shaping microbiota and vice versa (26,54), our current results imply that the compositional structure of microbiota is not strongly correlated to the expression patterns of host immune genes.…”
Section: Discussionsupporting
confidence: 53%
“…This system is also applicable for nitrogen removal in aquaculture, where increased nitrate concentration poses negative effects on fish (51). Indeed, the unclassified Comamonadaceae [AB076847, (42)] and Shinella spp., the intestinal abundance of which increased in response to the fucoidan feeding of adult zebrafish in our current study, have been reported to belong to denitrifying bacteria possessing biodegrading abilities of diverse compounds including biopolymers and xenobiotics (42,52,53). Therefore, it seems plausible that OM fucoidan may serve as a carbon source for intestinal bacteria of adult zebrafish, and identification of the degradation pathways involved awaits further investigation Although a large body of studies has documented that the host innate immunity plays significant roles for shaping microbiota and vice versa (26,54), our current results imply that the compositional structure of microbiota is not strongly correlated to the expression patterns of host immune genes.…”
Section: Discussionsupporting
confidence: 53%
“…However, the specific nicosulfuron biodegradation by the planktonic P. cucumerina AR1 was shown to be greater when the concentration of glucose decreased (Figure 4). This phenomenon has already been described for other pollutants (Ye et al, 2011; Shi et al, 2013; Wu et al, 2016). Indeed, the degradation efficiency increased with increasing concentration of glucose until an optimal concentration.…”
Section: Discussionsupporting
confidence: 71%
“…These isolates can most likely catalyze an oxidative mechanism involving a mono or dioxygenase, as was previously demonstrated [36]. In addition, several monooxygenases have been identified previously in strains similar to each of the four isolates, pointing to their potential in TBNPA and DBNPG oxidation [40][41][42][43][44][45][46]. For example, Pseudomonas citronellolis UAM-Ps1 co-metabolically transforms methyl tert-butyl ether (MTBE) to tertbutyl alcohol with n-pentane or n-octane as a gratuitous inducer of alkane hydroxylase (AlkB) [47].…”
Section: Microbial Isolatessupporting
confidence: 63%